diff --git a/documents/by-course/math-4b/course-notes/main.typ b/documents/by-course/math-4b/course-notes/main.typ index f42ac28..96b368e 100644 --- a/documents/by-course/math-4b/course-notes/main.typ +++ b/documents/by-course/math-4b/course-notes/main.typ @@ -67,6 +67,15 @@ Attendance to discussion sections is mandatory. - $y' = y^2$ ] +#definition[ + In general, a differential equation is called linear if and only if it can be + written in the form + $ + a_n (t) (dif^n y) / (dif t^n) + a_(n-1) (t) (d^(n-1) y) / (d t^(n-1)) + dots + a_1 (t) (dif y) / (dif t) + a_0 (t) y = g(t) + $ + where $a_k (t)$ and $g(t)$ are single variable functions of $t$. +] + #definition[ *Equilibrium solutions* for the ODE $ y' = F(x,y) $ @@ -87,3 +96,71 @@ Attendance to discussion sections is mandatory. What are the equilibria of the equation $ y' = y(y - x) $ ] + +== General solution of a first order linear ODE + +We start with the differential equation in standard form + +$ (dif y) / (dif t) + p(t) y = g(t) $ + +where $p(t)$ and $g(t)$ are continuous single variable functions of $t$. + +Then let us assume the existence of an *integrating factor* $mu(t)$, such that + +$ mu(t) p(t) = mu'(t) $ + +and then multiplying each term by $mu(t)$ to obtain + +$ mu(t) (dif y) / (dif t) + mu(t) p(t) y = mu(t) g(t) $ + +Then + +$ mu(t) (dif y) / (dif t) + mu'(t) y = mu(t) g(t) $ + +Then recognize that the left side of the equation is the product rule to obtain + +$ + (mu(t) y(t))' &= mu(t) g(t) \ + integral (mu(t) y(t))' dif t &= integral mu(t) g(t) dif t \ + mu(t) y(t) + C &= integral mu(t) g(t) dif t \ + y(t) &= (integral mu(t) g(t) dif t + C) / (mu(t)) +$ + +Now we have a general solution but we need to determine $mu(t)$. + +$ + mu(t) p(t) &= mu'(t) \ + (mu'(t)) / (mu(t)) &= p(t) \ + (ln mu(t))' &= p(t) +$ + +So now + +$ + integral mu(t) + k &= integral p(t) dif t \ + ln mu(t) &= integral p(t) dif t + k \ + mu(t) = e^(integral p(t) dif t + k) &= k e^(integral p(t) dif t) +$ + +Now substitute + +$ + y(t) &= (integral k e^(integral p(t) dif t) g(t) dif t + C) / (k e^(integral p(t))) \ + &= (k integral e^(integral p(t) dif t) g(t) dif t + C) / (k e^(integral p(t))) +$ + +Now do some cursed constant manipulation to obtain a final solution with only one arbitrary constant + +$ + y(t) = (integral e^(integral p(t) dif t) g(t) dif t + C) / (e^(integral p(t))) +$ + +#remark[ + The most useful result to us is + $ + y(t) &= (integral mu(t) g(t) dif t + C) / (mu(t)) \ + mu(t) &= e^(integral p(t) dif t) + $ + We can easily obtain a solution form for any first order linear ODE simply by + identifying $p(t)$ and $g(t)$. +] diff --git a/documents/by-course/math-6a/course-notes/main.typ b/documents/by-course/math-6a/course-notes/main.typ index 8fa6777..8c28c0f 100644 --- a/documents/by-course/math-6a/course-notes/main.typ +++ b/documents/by-course/math-6a/course-notes/main.typ @@ -59,3 +59,16 @@ point or vector. How far is the point $x_1, x_2, x_3$ from the origin? \ Answer: $x_1^2 + x_2^2 + x_3^2$ ] + +#definition[ + For vectors $u$ and $v$, where + $ v = vec(v_1, v_2, dots.v, n), u = vec(u_1, u_2, dots.v, n) $ + The dot product is defined as + $ sum_(i=1)^n v_i dot u_i $ +] + +#proposition[ + The dot product of two vectors is the product of their magnitudes and the cosine of the angle between. + + $ arrow(v) dot arrow(w) = ||arrow(v)|| dot ||arrow(w)|| cos theta $ +]